Pendidikan Akhlak Mulia sebagai Pilar Utama dalam ‎Pencegahan Bullying Siswa di MTs ‎Addini Al-Burdah ‎Dekatagung Sangkapura Gresik - Saiful Hasan (Jurnal Pendidikan Islam, 2025)
Bullying in schools is a significant issue that impacts students' psychological and academic ‎growth. Moral education serves as a critical pillar in preventing bullying at MTs Addini Al-‎Burdah Dekatagung Sangkapura Gresik. A qualitative-descriptive method was employed to ‎gather data through interviews, observations, and documentation. The findings reveal that ‎incorporating moral values such as empathy, tolerance, and respect into the curriculum and ‎school activities effectively reduced the number of bullying cases. Mentoring programs, ‎counseling guidance, and the reinforcement of school culture based on moral values fostered ‎a positive environment for shaping students' character. The study concludes that moral ‎education enhances moral awareness and promotes respectful behavior, significantly ‎preventing bullying. The study's limitation lies in its scope, which is restricted to a single ‎school, requiring broader validation of its findings. Recommendations include stronger ‎collaboration between schools and parents and enhanced teacher training in character ‎education.‎